THE IMPORTANCE OF STUDENTS' ADAB IN LEARNING - Ramadan Lubis; Ayu Aida Fitri; Ayu Safira (Sufiya Journal of Islamic Studies, 2023)
Adab is a very important part of education which deals with aspects of attitudes and values, both individuals and the values contained in religion that need to be known, understood, believed in and practiced by Indonesian people so that they can become the basis of personality so that they can become whole human beings. adab in life, even the smallest thing has its own rules. The purpose of this writing aims to describe the understanding of manners and manners of students in learning. In this study, the authors used a qualitative research method with a type of literature study. This method is descriptive and tends to use analysis in order to know or be able to describe the reality of the events studied, making it easier to obtain objective data in accordance with the facts. In etiquette learning, students should prioritize cleanliness of the soul over low morals, reduce worldly pleasures and stay away from home so that the heart is focused on knowledge, do not be arrogant or impetuous, and do not be disobedient to the teacher. A student of knowledge must have adab in order to receive blessings and find it easier to reach Allah SWT.